COMPARATIVE ANALYSIS OF MAMDANI AND SUGENO'S FUZZY INFERENCE METHOD ON ROOM LIGHT CONTROL PROTOTYPE - Sudianto Sudianto; Suhendra Anjar Dinata; Bagus Dwi Pandito; Deni Muharam; Purwani Husodo (Sean Institute, 2022)
Fuzzy Logic can be applied to the field of control systems. The advantage of using Fuzzy Logic is that it is easy to calculate because it combines mathematical equations and natural language. Therefore, Fuzzy Logic overcomes the weakness of the On/Off control system. Likewise, Fuzzy Logic overcomes the complexity of mathematical modeling on PID control. However, Fuzzy Logic is not suitable to be applied to control systems that require high accuracy. In this study, Fuzzy Logic will be applied to the control of room light, where in the room there are two light sources, namely lamp light and outside light. The problem is how the room light illuminance is always in the set point range with a tolerance of 25 lux and in steady state conditions. The application of light control is appropriate because it does not require high accuracy where a slight change in light illuminance has no effect. In this study, a comparison was made between the Mamdani and Sugeno inference methods. The limitation of control parameters is on the response of the control system to the set point. The results obtained are the control system response shows that there is a smaller error in the Sugeno method than the Mamdani method.